Pengaruh Komunikasi Interpersonal dan Quality Work of Life Terhadap Kinerja Pegawai Pada Dinas Pendidikan dan Kebudayaan Propinsi Maluku - Erlin Raitelu; Zainal Abidin Rengifurwarin; Elake Nataniel (Jurnal Ilmiah Global Education, 2026)
This study aims to examine the effect of interpersonal communication and quality of work life on employee performance at the Department of Education and Culture of Maluku Province. The study employed a descriptive quantitative approach with a causal correlational design. The population consisted of 296 employees, with 127 respondents selected through simple random sampling. Data were collected using a closed-ended questionnaire based on a Likert scale and analyzed using multiple linear regression. The findings reveal that interpersonal communication and quality of work life have a positive and significant effect on employee performance, both partially and simultaneously. Interpersonal communication shows a more dominant influence than quality of work life, indicating the importance of effective workplace interaction in improving employee performance. In addition, a supportive quality of work life contributes to increased motivation, comfort, and work productivity. This study provides practical implications for human resource management in public organizations, particularly in enhancing employee performance through strengthening interpersonal communication and improving quality of work life on a sustainable basis